The Role of Leaders' Motivation, Entrepreneurial Leadership, and Organisational Agility in Social Enterprise Sustainability - Jan, Brian Karno; Maulida, Mira (UI Scholars Hub, 2022)
Research Aims: Expand the insights for social enterprises (SEs) to sustain their economic and social performance, considering the impact of leader’s motivation, entrepreneurial leadership, organisational agility, and competitive advantage. Design/Methodology/Approach: The dataset was obtained from a survey of 102 SE strategic leaders in Indonesia, which was processed using PLS and SEM to test the hypothesis. Research Findings: Motivation has a positive effect on entrepreneurial leadership but not on organisational agility. Entrepreneurial leadership has tridirectionally relationships with organisational agility, competitive advantage, and social firm performance. Organisational agility has bidirectional relationships with competitive advantage and economic firm performance, whereas competitive advantage only positively affects social firm performance. Theoretical Contribution/Originality: Illuminated a way for SEs to improve economic and social performance by making several variables as a unit. So that SEs know where to put their focus and the impact of the decisions and steps they take. This study also paved the way for researchers to determine future research topics that must be explored. Managerial Implication in the South East Asian Context: As insights for SE leaders in making decisions and finding solutions to the challenges or problems they face while contributing to the development of organisational performance in terms of economic and social. Research Limitations & Implications: This study is a descriptive, cross-sectional study that only analyses Indonesian SEs. Therefore, this study's results only represent SE conditions at the specific time of this research.